UJI AKTIVITAS LARVASIDA PERASAN HERBA SELEDRI (Apium graveolens L.) TERHADAP LARVA Aedes aegypti - Dian Kartikasari; Mentari Novitasari (As-Syifaa Jurnal Farmasi, 2018)
The people of West Kalimantan tend to store water in water reservoirs around their homes, so that the water reservoirs are preferred to be used as breeding sites for Aedes aegypti mosquitoes. Prevention of the development of mosquitoes is very important, one program to suppress mosquito transmission is by eradicating larvae. The many negative effects of synthetic larvicides make the use of cytetic larvicides restricted, thus encouraging the development of natural larvicides, which are safe for the human body, easily accessible and environmentally friendly. Celery is one of the vegetable larvicides that is being developed by several researchers, so the purpose of this study is to determine the larvicidal activity of celery herb infused and to determine the concentration that can kill the most larvae and determine the values of LC50, LC100 and LT50, LT100. This research was conducted with a concentration of 1%, 2%, 3%, 4% and 5%, positive control (abate 0.01%) and negative aquadest control tested on 25 larvae for 24 hours. The results of this study showed the highest Mortality Percentage of mortality of Aedes aegypti larvae obtained from the infused of celery herbs (Apium graveolens L.) at a concentration of 5% which was 98.64%. Lethal concentration (LC50) infused of celery (Apium graveolens L.) as larvacide was 1.88%, LC100 4.43%, and Lethal Time (LT50) at 12.39 hours, LT100 at 29.42 hours